CONTINUOUS AMBULATORY PERITONEAL DIALYSIS USING STRAIGHT TYPE VS COILED TYPE TENCKHOFF CATHETER IN END-STAGE RENAL DISEASE PATIENTS AT SARDJITO HOSPITAL - Rahman, Eka Yudha; Rochadi, Sungsang; Utomo, Trisula (Indonesian Journal of Urology, 2011)
Objective: The purpose of this study was to compare straight type versus coiled type Tenckhoff catheter for continuous ambulatory peritoneal dialysis (CAPD) in end stage renal disease. Material & method: A prospective cohort study enrolled end-stage renal disease patients undergoing CAPD for renal replacement therapy in Urology and Nephrology Department, Sardjito Hospital from January to December 2007. Identity and type of Tenckhoff catheter were recorded. Patients were grouped into two groups who used straight type catheter and coiled type catheter for CAPD, then observed for post-operative complication. Statistical analysis was done using SPSS 14.0 with chi-square test. Results: There were 27 patients included in this study. The cause of end-stage renal disease was mostly DM and hypertension. The most common complication after  operation  was catheter  obstruction  (9 patients). Another complication was intraabdominal bleeding (1 patient), and catheter migration (1 patient). In patients with straight catheter (20 patients), there were 8 patients (40%) with complication. In patients with coiled catheter (7 patients), there were 3 patients (42%) with complication. There was no significant difference in complications between straight and coiled catheter groups (p = 0,895). Conclusion: The result of this study revealed that no significant difference in complication between straight and coiled catheter for CAPD in end-stage renal disease patients